2014
DOI: 10.22610/jebs.v6i1.465
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Prospects of Youth Entrepreneurship Development in a Designated Community in the Western Cape, South Africa

Abstract: In a job-scarce environment, where unemployment is rife the need for fostering entrepreneurship especially among youth is a prime concern. This is arguably the case in South Africa, where despite a number of government-pioneered interventions, the level of youth entrepreneurship, particularly in township areas remains unsatisfactory. This study takes a two-pronged approach to establish specific factors that are inhibiting youth entrepreneurship development, and determine the prospects of youth entrepreneurship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 5 publications
1
21
0
1
Order By: Relevance
“…It is also found that parents and society have the belief that the white-collar jobs are superior to entrepreneurship which gives the youth the mindset that in order for them to survive and become successful they have to work for other people. In Zambia, Masanta (2017) found that there was great potential for the youth to participate in entrepreneurial activities, the study conducted by Gwija, Eresia-Eke & Iwu (2014) revealed that South African youth faces wide range of challenges which are: lack of start-up and development capital, absence of government support, red tape, labour laws and harsh business regulation and inappropriate entrepreneurship education.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It is also found that parents and society have the belief that the white-collar jobs are superior to entrepreneurship which gives the youth the mindset that in order for them to survive and become successful they have to work for other people. In Zambia, Masanta (2017) found that there was great potential for the youth to participate in entrepreneurial activities, the study conducted by Gwija, Eresia-Eke & Iwu (2014) revealed that South African youth faces wide range of challenges which are: lack of start-up and development capital, absence of government support, red tape, labour laws and harsh business regulation and inappropriate entrepreneurship education.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…To cope with sudden business changes, new firms need to have the necessary management and entrepreneurial skills to start and sustain their business, unfortunately, the opposite is the case in most developing countries in general and the Kingdom of Eswatini in particular. Gwija et al (2014) in their study, noted that education and training in entrepreneurship could positively contribute to the success of any business. The developed routine through experiential practice reshapes the operation of a start-up venture.…”
Section: Facilitating Entrepreneurial Skillsmentioning
confidence: 96%
“…Acquiring business funding is a challenge to most SMEs, not just in Eswatini but in many emerging countries. Aspiring entrepreneurs in Khayelitsha, South Africa, who cannot afford to raise capital, due to a lack of funding, opt for paid jobs (Gwija et al, 2014). Unfortunately, this includes graduates who have acquired entrepreneurship education from the university.…”
Section: Provision Of Strategic Support To Equip Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain itu, adanya keterampilan berwirausaha dapat memperbaiki pengembangan dan keberlanjutan usaha (Lose & Tengeh, 2015). Dengan demikian, sudah selayaknya bila keterampilan berwirausaha dapat diajarkan mulai dari sekolah menengah hingga perguruan tinggi agar lebih dapat menciptakan pekerjaan sendiri daripada menjadi pencari pekerjaan (Gwija, Eke, & Iwu, 2014).…”
Section: Tinjauan Pustakaunclassified